2020
DOI: 10.1108/ijoem-01-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of energy intensity in Indonesia

Abstract: PurposeIndonesia is the fourth most populous country in the world, which has a strong effect on primary energy use and depletion of natural resources. This paper considers energy intensity (EI) defined as a measure of the amount of energy it takes to produce a dollar's worth of economic output. The purpose of the paper is to explore how different factors contributed to the decline in Indonesia's EI.Design/methodology/approachThe cointegration regression methodology is applied to explore the long-term nexus bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 87 publications
0
3
0
1
Order By: Relevance
“…Also, Su-yun and Su-yun and Zhen-yu (2010) confirmed a positive effect of trade on energy intensity. Yu et al (2022) have found for a group of 82 countries that trade worsens energy intensity likewise the findings of Zhang et al (2019) for China, and Rudenko and Tanasov (2020) for Indonesia. A threshold analysis by Yu et al (2022) provided mixed evidence regarding the effect of trade openness.…”
Section: Brief Literature Reviewmentioning
confidence: 67%
See 1 more Smart Citation
“…Also, Su-yun and Su-yun and Zhen-yu (2010) confirmed a positive effect of trade on energy intensity. Yu et al (2022) have found for a group of 82 countries that trade worsens energy intensity likewise the findings of Zhang et al (2019) for China, and Rudenko and Tanasov (2020) for Indonesia. A threshold analysis by Yu et al (2022) provided mixed evidence regarding the effect of trade openness.…”
Section: Brief Literature Reviewmentioning
confidence: 67%
“…Regarding income, its ability to enhance the adoption of energy-efficient technology or energy-intensive goods determines whether it will reduce or increase energy intensity (Kwakwa, 2019). Empirical findings have been mixed on the effects of income and trade openness on energy intensity (Cole, 2006; Kwakwa and Adusah-Poku, 2019; Rudenko and Tanasov, 2020), giving room for more studies. Also, existing studies have been silent on the role of renewable energy and trade openness when it comes to the effect of income on energy intensity nexus.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, industrial production frequently uses more energy than the service industry. From earlier researches, (Sineviciene et al, 2017), (Filipovic et al, 2015) and (Sadorsky, 2013), (Rudenko & Tanasov, 2022). Energy efficiency is reduced by 1.90, 0.32 and 0.74 units in FMOLS, DOLS and CCR for every unit growth in industry value added in China.…”
Section: Resultsmentioning
confidence: 86%
“…Penelitian ini menjadi penting karena penggunaan energi listrik semakin berkembang dan tantangan untuk merubah energi fosil ke EBT menjadi perhatian utama hampir seluruh dunia utamanya karena alasan lingkungan dan penyelamatan keberlangsungan alam ini [14] [15]. Kebijakan Energi Nasional mengacu pada Paris Agreement tahun 2015 telah ditindaklanjuti dengan komitmen mewujudkan Net zero emissions pada tahun 2050 dengan perjanjian aliansi keuangan yang dibuat pada tahun 2021 telah menciptakan perubahan yang strategis, sebagai dukungan Paris Agreement 2015 berpengaruh terhadap peran pembiayaan global saat ini [8]. Terdapat 2 pengaruh besar yang oleh kebijakan Paris Agreement dari sisi pembiayaan yaitu, pertama divestasi pada aset intensif karbon dan kedua, memobilisasi kapital ke arah aset transisi energi rendah karbon.…”
Section: Pendahuluanunclassified